Mothers' employment in wealthy countries: How do cultural and institutional factors shape the motherhood employment and working hours gap? - Irene Boeckmann; Joya Misra; Michelle Budig (Luxembourg Income Study (LIS), 2013)
Existing research shows that women's employment patterns are not so much driven by gender, as by gendered parenthood, with childless women and men (including fathers) employed at substantially higher levels than mothers in most countries. We focus on the cross-national variation in the gap in employment participation and working time between mothers and women without children in the same household. This variation remains salient, even when we control for individual and household-level factors, such as human capital, partnered status, and household income. We provide evidence that institutional and cultural contexts shape their opportunities in important ways: more generous paid leaves, publicly supported childcare services for very young children, and cultural support for maternal employment predict lower differences in employment participation and working hours between mothers and childless women, while the length of job protected leave is associated with larger motherhood employment gaps.
Keywords: 330